Acute Embolic Stroke as the Sole Presentation of Infective Endocarditis in Mitral Valve Prolapse - Andreas Hartanto Santoso; Leonardo Paskah Suciadi; Frandy Susatia (PT Kalbe Farma Tbk., 2019)
Case: A 43 yo. male was hospitalized with acute drowsiness and left-sided hemiparesis. Stroke was confirmed by head CT scan. Diagnosis of definite infective endocarditis (IE) was made by 1 major criterion (vegetation at mitral valve on echocardiography) and 3 minor criteria (mitral valve prolapse, persistent fever, and stroke). However, blood cultures were negative presumably due to early antibiotics administration. He was treated with parenteral antibiotics for 10 days, and continued with outpatient parenteral antibiotic therapy (OPAT). A clinical improvement was observed. Conclusion: Acute stroke can be an early manifestation of IE without any cardiac symptoms. Kasus: Laki-laki usia 43 tahun masuk rumah sakit dengan penurunan kesadaran dan hemiparesis sinistra. CT scan kepala sesuai gambaran stroke non-hemoragik. Diagnosis endokarditis infektif ditegakkan berdasarkan kriteria Duke, yaitu 1 kriteria mayor (vegetasi katup mitral pada ekokardiografi) dan 3 kriteria minor (prolapsus katup mitral sebagai faktor predisposisi, demam menetap, dan stroke). Hasil kultur darah negatif dapat disebabkan pemberian antibiotik dini. Pasien diterapi dengan antibiotik parenteral selama 10 hari di rumah sakit dilanjutkan pada rawat jalan. Kondisi klinis pasien membaik. Simpulan: Stroke akut dapat merupakan manifestasi awal endokarditis infektif, meskipun tanpa keluhan jantung.